Do Peers Affect Student Achievement in China's Secondary Schools? - Ding, Weili; Lehrer, Steven F (The Review of Economics and Statistics, 2007)
Peer effects have figured prominently in debates on school vouchers, desegregation, ability tracking, and antipoverty programs. Compelling evidence of their existence remains scarce for plaguing endogeneity issues such as selection bias and the reflection problem. This paper is among the first to firmly establish the link between peer performance and student achievement, using a unique data set from China. We find strong evidence that peer effects exist and operate in a positive and nonlinear manner; reducing the variation of peer performance increases achievement; and our semiparametric estimates clarify the trade-offs facing policymakers in exploiting positive peer effects to increase future achievement.